Linear programming problems in High School using GeoGebra - Cerqueira, Gonçalo Renildo; Pires, Velton Cardoso; Campos, Daniel Silva (Revista de Ciência da Computação, 2021)
Many high school teachers when teaching mathematical content, face questions from their students about the applicability of these contents. We will show in this paper that it is possible to answer some of these questions by relating some of this content to optimization problems, which are modeled as linear programming problems and solved using GeoGebra as a tool.